A survey of free glutamic acid in foods using a robust LC-MS/MS method - Cebi, Nur; Dogan, Canan Ekinci; Olgun, Elmas Oktem; Sagdic, Osman (ELSEVIER SCI LTD, 2018)
An effective and simultaneous liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was used with the aim of quantifying monosodium glutamate (MSG) in foodstuffs, such as chips, taste cubes, sauces and soups. The results were linear (R-2 = 1), with very low LOD and LOQ values, 1.0 mu g/kg, 5.0 mu g/kg, respectively. Excellent repeatability and reproducibility were also achieved. This highly sensitive and robust LC-MS/MS technique was applied successfully for the detection and quantification of MSG in a wide variety of foodstuffs. MSG contents ranged from 0.01 g/100 g to 15.39 g/100 g in food samples. Importantly, determination of free glutamic acid in the daily diet could also prevent various side effects associated with consumption of excess free glutamic acid.
Keywords: MSG; Monosodium glutamate; HPLC; Tandem mass; LC-MS/MS; CHROMATOGRAPHY-MASS SPECTROMETRY; AMINO-ACIDS; Chemistry; Food Science & Technology; Nutrition & Dietetics